Are We Still Cheap on Crime? Austerity, Punitivism, and Common Sense in the Trump/Sessions/Barr Era - Aviram, Hadar (2020)
Literature on “late mass incarceration” observed a contraction of the carceral state, with varying opinions as to its causes and varying degrees of optimism about its potential. But even optimistic commentators were taken aback by the Trump-Sessions administration’s criminal justice rhetoric. This paper maps out the extent to which federal, state, and local actions in the age of Trump have reversed the promising trends to shrink the criminal justice apparatus, focusing on federal legislation, continued state and local reform, and the role of criminal justice in 2020 presidential campaigns. The paper concludes that the overall salutary trends from 2008 onward have slowed down in some respects, but continued on in others, and that advocacy concerns should focus on particular areas of the criminal justice apparatus, especially immigration and the federal war on drugs